Optical Properties of Silicon Nanoparticles Prepared by Laser Ablation Method in Various Media - Tuan, Chu Anh; Trang, Nguyen Thi Thu; Tu, Le Anh; Giang, Duong Thi; Duong, Pham Hong; Huy, Pham Thanh (Communications in Physics, 2014)
Bright photoluminescent silicon nanoparticles were successfully fabricated from porous silicon target in air and n-hexane using 532 nm line of YAG:Nd pulsed laser. The whole procedure was carried out at room temperature, in atmosphere. The morphology and composition of as-synthesized nanoparticles were characterized by SEM and EDS measurements. Their optical properties were investigated. The PL peak position of the as-synthesized Si nanoparticle ablated in air is slightly blue-shifted in comparison with those ablated in n-hexane, while it was almost no change of peak position of Si nanoparticles fabricated from p-Si in hexane and original p-Si wafer target. In contrast to PL intensity quenching of original p-Si sample and particles produced in air, those produced in n-hexane solvent exhibited an enhancement. The presence of dangling bonds or energy transfer from excited Si particles to oxygen molecules on the surface can be the cause of the quenching effect.